Association Between Motor and Cognitive Performances in Elderly With Atrial Fibrillation: Strat-AF Study - Salvadori, Emilia; Galmozzi, Francesco; Uda, Francesca; Barbato, Carmen; Camilleri, Eleonora; Cesari, Francesca; Chiti, Stefano; Diciotti, Stefano; Donnini, Samira; Formelli, Benedetta; Galora, Silvia; Giusti, Betti; et al. (Frontiers in Neurology, 2020)
Background/Objective. Growing evidence suggests a close relationship between motor and cognitive abilities, but possible common underlying mechanisms are not well established. Atrial fibrillation (AF) is associated with reduced physical performance and increased risk of cognitive decline. The study aimed to assess in a cohort of elderly AF patients: 1) the association between motor and cognitive performances and 2) the influence and potential mediating role of cerebral lesions burden. Design. Strat-AF is a prospective, observational study investigating biological markers for cerebral bleeding risk stratification in AF patients on oral anticoagulants. Baseline cross-sectional data are here presented. Setting. Thrombosis Centre outpatient-clinic (Careggi-University Hospital). Participants. One-hundred and seventy patients (mean age 77.7±6.8; females 35%). Measurements. Baseline protocol included: neuropsychological battery, motor assessment (Short Physical Performance Battery - SPPB, and walking speed), and brain magnetic resonance imaging (MRI) used for the visual assessment of white matter hyperintensities, lacunar and non-lacunar infarcts, cerebral microbleeds, global cortical and medial temporal atrophies. Results. Mean Montreal Cognitive Assessment (MoCA) total score was 21.9±3.9, SPPB total score 9.5±2.2, and walking speed 0.9±0.2. In univariate analyses, both SPPB and walking speed were significantly associated with MoCA (r=.359, r=.372, respectively), Visual search (r=.361, r=.322), Stroop (r=-.272, r=-.263), Short story (r=.263, r=.310) and Semantic fluency (r=.311, r=.360). In multivariate models adjusted for demographics, heart failure, physical activity and either stroke history (Model 1) or neuroimaging markers (Model 2), both SPPB and walking speed were confirmed significantly associated with MoCA (Model 1: β=.256, β=.236; Model 2: β=.276, β=.272, respectively), Visual Search (Model 1: β=.350, β=.313; Model 2: β=.344, β=.307), semantic fluency (Model 1: β=.223, β=.261), and short story (Model 2: β=.245, β=.273). Conclusions. In our cohort of elderly AF patients, a direct association between motor and cognitive functions consistently recurred using different evaluation of the performances, without an evident mediating role of cerebral lesions burden.